Persepsi Mahasiswa Terhadap Peningkatan Skill Digitalisasi Melalui Program MBKM Studi Independen Bersertifikat di RevoU Tech Academy - Salsabila, Hana (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
Technological advancements drive industries to transition to the digital realm, producing new jobs. To minimize unemployment in Indonesia, the government is combining education and the industrial sector through the Independent Study Independent Study Campus (MBKM) initiative. The purpose of this study is to examine how students perceive the Certified Independent Study MBKM curriculum at RevoU Tech Academy for enhancing their digital abilities. This study employs a qualitative approach with interviews as the data gathering technique, with students who have participated in these events. Thus, it is planned that this research will detail the learning process, the problems encountered during the program, and the program's influence on developing students' digital abilities and preparation to meet the needs of an increasingly digital work market.